Recessions after Systemic Banking Crises: Does it matter how Governments intervene? - Sweder van Wijnbergen; Timotej Homar (Tinbergen Institute, 2013)
Systemic banking crises often continue into recessions with large output losses (Reinhart & Rogoff 2009a). In this paper we ask whether the way Governments intervene in the financial sector has an impact on the economy's subsequent performance. Our theoretical analysis focuses on bank incentives to manage bad loans. We show that interventions involving bank restructuring provide banks with incentives to restructure bad loans and free up resources for new economic activity. Other interventions lead banks to roll over bad loans, tying up resources in distressed firms. Our analysis suggests that zombie banks are a drag on economic recovery. We then analyze 65 systemic banking crises from the period 1980-2012, of which 25 are part of the recent global financial crisis, to answer the question: how effective are intervention measures from the macro perspective, in particular how do they affect recession duration? We find that bank restructuring, which includes bank recapitalizations, significantly reduces recession duration. The effect of liquidity support on the probability of recovery is positive but smaller. Blanket guarantees on bank liabilities and monetary policy do not have a significant effect.
Keywords: E44; E58; G21; G28; 330; Financial crises; intervention policies; zombie banks; economic recovery; bank restructuring; bank recapitalization